Clinicopathological Features of a Lower Lip Verruciform Xanthoma: A Rare Case Report - Sayali Goraksha Lokhande; Sunil Surendra prasad Mishra; Bharti Eknath Helge; Ashutosh Sanjay Dighe (Journal of Clinical and Diagnostic Research, 2024)
Verruciform Xanthoma (VX) is an uncommon, benign, asymptomatic lesion of the oral cavity. The incidence rate of VX is 0.025%, with the most common location reported to be the gingival margin, followed by the tongue, hard palate, buccal and labial mucosa. It may also present on the skin and genitals. VX can manifest as a solitary or multiple lesion with well-defined margins. It appears as a papule or plaque with verrucous or papillary growth, exhibiting variable colours ranging from reddish-pink and yellow to grey. While the lesion typically appears verruciform, it may also have a polypoid, papillomatous, or sessile nature. In the present case report, the authors present a 45-year-old male patient with a history of tobacco use, who exhibited a reddish-pink papillomatous growth on his labial mucosa for a duration of three months. The growth was surgically excised, and histopathological evaluation confirmed the characteristic features of VX. The lesion healed without complications, and no recurrence was observed. Clinically, VX may be mistaken for various malignant or premalignant lesions such as papilloma, verrucous carcinoma, or proliferative verrucous leukoplakia. Therefore, it is crucial to differentiate VX from these conditions to avoid inappropriate intervention. Histopathological evaluation is necessary for the definitive diagnosis of the lesion, which reveals the pathognomonic presence of foamy histiocytes within the elongated dermal papillae. The present case report highlighted the diverse clinical features of VX and discusses its histological findings along with the differential diagnosis.